2013
DOI: 10.3109/14015439.2013.825640
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic consequences from changing voice ideals (clear to harsh, pleasant to jarring): Summarizing report on a round-table discussion at the 5th World Voice Congress, Luxor, Egypt, 27–31 October 2012

Abstract: Starting out with an attempt to define an 'ideal voice', the discussion moved on to the hazards of pop singing, followed by the topics of harsh voices (from the desired effects in modern singing expression to devastating clinical cases), phoniatric targets (aesthetics and fitness), and, finally, the phoniatricians' attitudes comprising acceptance, neglect, and rejection. Therapy should aim at a resilient and effective voice regardless of the mere sound, unless the perfection of the vocal sound is the ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, this style can lead to a devastating voice disorder. Vocal rehabilitation for artists with intentional distortions should aim at a resilient and effective voice regardless of the sound [61]. It is possible to produce a healthy distorted sound for a specific market purpose, but no studies have focused on this issue.…”
Section: Effectiveness Of Voice Training and Treatment Programsmentioning
confidence: 98%
“…However, this style can lead to a devastating voice disorder. Vocal rehabilitation for artists with intentional distortions should aim at a resilient and effective voice regardless of the sound [61]. It is possible to produce a healthy distorted sound for a specific market purpose, but no studies have focused on this issue.…”
Section: Effectiveness Of Voice Training and Treatment Programsmentioning
confidence: 98%
“…Nowadays breathy, distorted, and affected voices are common in contemporary non-classical singing and it has been reported that there are ways to teach them in a healthy way. For instance, the level of glottal closure is crucial for a good and safe way to use a breathy voice, and a distorted sound has to be produced with free and pressureless use of the ventricular folds [37]. Similarly, the techniques commonly applied in heavy metal style of singing: growl voice and reinforced falsetto seem to perceptually be a pressed and laryngeal hyperfunctional voice, classically labeled as vocal abuse.…”
Section: Is Non-classical Style Of Singing Detrimental To Vocal Health?mentioning
confidence: 99%